ELECTRONIC MAILING LIST AND INTERNET FORUMS - TOOLS FOR MANAGEMENT AND MARKETING WITHIN EDUCATIONAL ORGANIZATIONS - Dorin Cristian COITA; Maria Madela ABRUDAN (Management & Marketing)
This paper is about the use of Electronic Mailing List and Internet Forums as tools for managers within educational organizations. In the same time, some of concepts, ideas and models can be used in other business organizations, especially in service providing organizations. Understanding management requires both learning and practicing, directly experiencing. People involved in electronic networks are experiencing the alternative to real communication. We considered Electronic Mailing List and Internet Forums both as marketing tool and a human resources management tool. The benefits of using discussion lists are: people informed, involved and improved.